A film and its preparation method and application
By designing a film including a thermoplastic base layer, a functional layer and a thermoplastic base layer, the problem that the existing film cannot take into account both the transmission performance and the thermal insulation performance is solved, and efficient thermal insulation and light transmission effects are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411980437.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-31
Smart Images

Figure CN119388860B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer films, and in particular to a film and a preparation method and application thereof. Background Art
[0002] Sunscreen decorative films are generally prepared by sputtering coating or evaporation coating. Sputtering and evaporation have high energy consumption and high coating production temperature, and are not suitable for coating thermoplastic film materials. In addition, the production efficiency is low and the cost is high, and the commercialization cost is high. In addition, most of the existing sunscreen decorative films use light blocking or reflection technology to achieve heat insulation, which has a great impact on lighting and cannot take into account both transmittance and heat insulation performance. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defect of the existing film that it cannot achieve excellent permeability and heat insulation performance at the same time, thereby providing a film and a preparation method and application thereof.
[0004] The first aspect of the present invention protects a film, wherein the film comprises a first thermoplastic base layer, a functional layer, and a second thermoplastic base layer arranged in sequence from bottom to top;
[0005] in,
[0006] A continuous first groove is arranged on the surface of the first thermoplastic base layer, a second groove is arranged between two adjacent first grooves, the second grooves share a groove edge with the two adjacent first grooves, the spatial shape of the second grooves is the same as the spatial shape of the first grooves, and the groove shapes are inverted with each other, the spatial shape is a triangular pyramid, and the dyne value of the surface is 36-58 dyn / cm;
[0007] The surface of the second thermoplastic base layer is flat, and the dyne value of the surface is 36-58 dyn / cm;
[0008] The functional layer includes an anti-reflection layer and a metal reflective layer; the metal reflective layer is arranged on the anti-reflection layer;
[0009] The bottom of the functional layer is in contact with the surface of the first thermoplastic base layer, and the shape of the upper surface of the functional layer is the same as the shape of the surface of the first thermoplastic base layer.
[0010] In the present invention, the first thermoplastic base layer and the functional layer are connected via polar groups and free radical groups, so that the adhesion is closer.
[0011] In the present invention, the dyne value is the sum of the free radical group and the polar group, and the dyne value is tested using a dyne solution or a surface tension meter. The thickness of each layer is tested using a Cary 5000 Agilent UV-Vis-NIR spectrophotometer.
[0012] According to the present invention, the isosceles triangle on the side of the triangular pyramid is an isosceles right triangle, and the side length of the equilateral triangle on the bottom is 1-5 μm.
[0013] According to the present invention, the materials of the first thermoplastic base layer and the second thermoplastic base layer are at least one of PVC (polyvinyl chloride), PP (polypropylene), PET (polyethylene terephthalate), TPU (thermoplastic polyurethane), and PU (polyurethane).
[0014] According to the present invention, the thickness of the first thermoplastic base layer is 0.1-0.5 mm, and the thickness of the second thermoplastic base layer is 0.05-0.2 mm.
[0015] According to the present invention, the refractive index of the second thermoplastic base layer is less than or equal to the refractive index of the first thermoplastic base layer. When the second thermoplastic base layer and the first thermoplastic base layer are made of the same material, their refractive indices are the same. The present invention uses conventional methods to test the refractive index.
[0016] According to the present invention, the material of the anti-reflection layer includes inorganic oxides and / or inorganic halides, and can be selected from at least one of silicon dioxide, titanium dioxide, aluminum oxide, and calcium fluoride, and can further be selected from silicon dioxide.
[0017] According to the present invention, the thickness of the anti-reflection layer is 120-150 nm.
[0018] According to the present invention, the material of the metal reflective layer is a reflective metal, including at least one of gold, silver, and aluminum, and can further be silver.
[0019] According to the present invention, the thickness of the metal reflective layer is 40-1300 nm, and can be optionally 40-100 nm.
[0020] The second aspect of the present invention protects a method for preparing the aforementioned film, wherein the preparation method comprises the following steps:
[0021] S1, preparing a first groove and a second groove arranged continuously on one side surface of a first thermoplastic base layer, and performing plasma treatment, performing plasma treatment on the surface of the second thermoplastic base layer, the dyne value of the surface of the first thermoplastic base layer is 36-58 dyn / cm, and the dyne value of the surface of the second thermoplastic base layer is 36-58 dyn / cm; wherein the second groove shares a notch edge with two adjacent first grooves, the spatial shape of the second groove is the same as the spatial shape of the first groove, and the notch shapes are inverted, and the spatial shape is a triangular pyramid;
[0022] S2, preparing an anti-reflection layer on the upper surface of the first thermoplastic base layer treated in step S1, and preparing a metal reflective layer on the upper surface of the anti-reflection layer to obtain a functional layer;
[0023] S3, laminating the second thermoplastic base layer processed in step S1 with the product obtained in step S2 to obtain a laminating film.
[0024] In the present invention, ultrasonic waves are used to clean the surface of the material before plasma treatment.
[0025] In the present invention, the types of specific materials have been described in the first aspect of the protection content and will not be repeated here.
[0026] In the present invention, a silicone roller or other embossing tools are used to emboss the surface of the first thermoplastic base layer to prepare the first groove and the second groove.
[0027] According to the present invention, the isosceles triangle on the side of the triangular pyramid is an isosceles right triangle, and the side length of the equilateral triangle on the bottom is 1-5 μm.
[0028] In S1 of the present invention, the specific preparation steps of the plasma treatment are conventional preparation methods in the art, typically but not limitingly, an ion cleaner or a corona machine is used to ionize the layer surface.
[0029] According to the present invention, in S2, the raw material components of the transmittance-enhancing layer material are reacted in an ultrasonic environment using the principle of ultrasonic cavitation to prepare a crystal nucleus solution with a particle size of less than 20 nm. Under vacuum, the crystal nucleus solution is coated on one side surface of the treated first thermoplastic layer by a first ultrasonic atomization spray, and then a first microwave irradiation vibration heating is performed to crystallize and deposit the crystal nucleus solution, and the transmittance-enhancing layer is obtained after drying. The material of the transmittance-enhancing layer of the present invention is described in the first aspect of the present invention, and the types and amounts of the raw materials are conventional in the art. When the material of the transmittance-enhancing layer is silicon dioxide, typically and non-limitingly, the specific preparation steps are as follows: in a sodium metasilicate aqueous solution with a concentration not higher than 15wt%, 1wt% polyvinyl alcohol is added as a stabilizer and acts as an adhesive, an ultrasonic machine is turned on in the reaction container for dispersion and mixing, and then 0.1mol / L hydrochloric acid solution is slowly added, the molar ratio of sodium metasilicate to hydrogen chloride is 1:2, the reaction is slightly excessive with the hydrochloric acid solution, the dropping time is controlled at 1-3h, and the dropping speed is not too fast to prepare a crystal nucleus solution with a particle size of less than 20nm.
[0030] According to the present invention, the ultrasonic operating frequency of the first ultrasonic atomization spraying is 20-100 GHz and the temperature is 30-80°C.
[0031] According to the present invention, the frequency of the first microwave is 2-3 GHz, and the temperature is 50-150°C.
[0032] According to the present invention, the step of preparing the metal reflective layer includes: applying the nano metal solution obtained by the silver mirror reaction to the anti-reflection layer by a second ultrasonic atomization spray under vacuum, and then performing a second microwave irradiation vibration heating to make the nano metal solution crystallize and deposit on the surface of the anti-reflection layer, drying and performing a second microwave irradiation, and sintering the product after crystallization and deposition to obtain a metal film layer. The average size of the metal particles is below 20nm. When the metal is silver, the nano silver with a size below 20nm has a melting point as low as 100°C, and the film is formed by microwave sintering at low temperature, and the metal film layer is obtained by microwave drying and low temperature sintering; the silver mirror reaction is a conventional silver mirror reaction in the art, and typically, non-limitingly, the specific preparation step process is: the silver ammonia solution is prepared and used immediately, the molar ratio of diammine silver hydroxide in the silver ammonia solution and glucose in the glucose solution is 2:1, and 1wt% of polyvinyl alcohol is added, and after the reaction, the nano metal solution is applied to the anti-reflection layer by a metering pump into an ultrasonic atomization spray device.
[0033] According to the present invention, the ultrasonic operating frequency of the second ultrasonic atomization spraying is 20-100 GHz and the temperature is 30-80°C.
[0034] According to the present invention, the frequency of the second microwave is 2-3 GHz, and the temperature is 100-150°C.
[0035] According to the present invention, the specific preparation steps of the ultrasonic vacuum bonding include: In S3, the specific bonding steps include: in vacuum, using ultrasonic method to bond multiple groups of double-wheel solid film layers to obtain a bonded film.
[0036] According to the present invention, the temperature of the ultrasonic bonding is 50-160°C.
[0037] The third aspect of the present invention protects the use of the aforementioned film or the film prepared by the aforementioned preparation method in sun-proof and heat-insulating films, typically but not limitedly, including application in building door and window glass and automobile glass.
[0038] The technical solution of the present invention has the following advantages:
[0039] 1. The present invention provides a film, wherein the film comprises a first thermoplastic base layer, a functional layer, and a second thermoplastic base layer arranged in sequence from bottom to top; wherein a continuous first groove is arranged on the surface of the first thermoplastic base layer, a second groove is arranged between two adjacent first grooves, the second grooves share a groove edge with the two adjacent first grooves, the spatial shape of the second groove is the same as the spatial shape of the first groove, and the groove shapes are inverted, the spatial shape is a triangular pyramid, and the dyne value of the surface is 36-58dyn / cm; the surface of the second thermoplastic base layer is a plane, and the dyne value of the surface is 36-58dyn / cm; the functional layer comprises an anti-reflection layer and a metal reflective layer; the metal reflective layer is arranged on the anti-reflection layer; the bottom of the functional layer is bonded to the surface of the first thermoplastic base layer, and the upper surface shape of the functional layer is the same as the surface shape of the first thermoplastic base layer. The film of the present invention can take into account both light transmittance and heat insulation performance. The bottom of the functional layer is bonded to the surface of the first thermoplastic base layer, the overall surface area involved in the reflection is increased, and it has a better reflectivity for infrared light. By reflecting infrared light, heat accumulation is prevented to achieve heat insulation and sun protection. The anti-reflection layer in the functional layer can improve the transmittance of the film and also make the film present good aesthetic performance, while the metal reflective layer can improve the reflectivity. After the film layers are bonded, the functional layer and the space on the surface of the second thermoplastic base layer form countless tiny vacuum cavities, which improves the thermal insulation performance of the film. The specific dyne value makes the film layers fit more closely, the film has good density, and the stability of the film is improved. Also, because the film layers are tighter and thinner, the permeability of the film is increased.
[0040] 2. In the present invention, when the refractive index of the second thermoplastic base layer is smaller than the refractive index of the first thermoplastic base layer, the refractive effect can be further improved.
[0041] 3. In the present invention, when the thickness of the metal reflective layer meets a specific range, the transmittance of visible light can be further improved, achieving a balance between visible light transmittance and infrared light reflection.
[0042] 4. The present invention provides a method for preparing a film, wherein the preparation method comprises the following steps: S1, preparing a first groove and a second groove arranged continuously on one side surface of a first thermoplastic base layer, and performing plasma treatment, performing plasma treatment on the surface of a second thermoplastic base layer, the dyne value of the surface of the first thermoplastic base layer is 36-58dyn / cm, and the dyne value of the surface of the second thermoplastic base layer is 36-58dyn / cm; wherein the second groove shares a notch edge with two adjacent first grooves, the spatial shape of the second groove is the same as the spatial shape of the first groove, and the notch shapes are inverted, and the spatial shape is a triangular pyramid; S2, preparing an anti-reflection layer on the upper surface of the first thermoplastic base layer treated in step S1, and preparing a metal reflective layer on the upper surface of the anti-reflection layer to obtain a functional layer; S3, laminating the second thermoplastic base layer treated in step S1 with the product obtained in step S2 to obtain a film. The preparation method of the present invention uses a layer-by-layer laminating technology to make the lamination between the various film layers more closely, improve the density of the film, and make the film have excellent thermal insulation and reflection properties.
[0043] 5. When preparing the anti-reflection layer and the metal reflective layer, the present invention adopts the method of ultrasonic atomization spraying under vacuum conditions and then microwave high-frequency vibration. Compared with the vacuum evaporation film or sputtering coating method used in existing film pasting, it can reduce energy consumption and improve efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 is a cross-sectional schematic diagram of the film of Example 1;
[0046] Figure 2 It is a schematic diagram of the structure of a single triangular pyramid in Example 1;
[0047] Figure 3 This is a schematic diagram of the top view of the film of Example 1;
[0048] Reference numerals:
[0049] 1. First thermoplastic base layer; 2. Anti-reflection layer; 3. Metal reflective layer; 4. Second thermoplastic base layer; 5. Vacuum cavity; a. First groove; b. Second groove. DETAILED DESCRIPTION
[0050] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0051] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0052] Experimental equipment: vacuum box, with ultrasonic atomization spray device on the top, winding and unwinding devices inside the box, a surface ion cleaning machine on the unwinding device to perform ion cleaning on the surface of the film, and a microwave high-frequency transmitter in the rear section.
[0053] The first PVC layer with a thickness of 0.18 mm was purchased from Guangdong Tianan New Materials Co., Ltd.;
[0054] The second PVC layer with a thickness of 0.1 mm was purchased from Guangdong Tianan New Materials Co., Ltd.
[0055] Example 1
[0056] This embodiment provides a method for preparing a film, and the cross-sectional schematic diagram is as follows Figure 1 As shown in the figure, the first thermoplastic base layer 1, the anti-reflection layer 2, the metal reflective layer 3, the second thermoplastic base layer 4, and the vacuum cavity 5 can be seen. The schematic diagram of a single triangular pyramid structure is shown in Figure 2 As shown, the top view of the film is shown in Figure 3 As shown, the specific steps include:
[0057] S1, embossing the surface of the first PVC layer by a silicone wheel to prepare continuously arranged first grooves, a second groove b is arranged between two adjacent first grooves a, the second grooves share a groove edge with the first grooves on both sides, the spatial shape of the second grooves is the same as the spatial shape of the first grooves, and the groove shapes are inverted, the spatial shape is a triangular pyramid, the isosceles triangle on the side of the triangular pyramid is an isosceles right triangle, and the side length of the equilateral triangle on the bottom is 2 μm, the surfaces of the first PVC layer and the second PVC layer are cleaned by ultrasonic wave, and then the surfaces are plasma treated by an ion cleaning machine, the dyne value of the surface of the first PVC layer after treatment is 36 dyn / cm, the refractive index is 1.54, and the dyne value of the surface of the second PVC layer is 36 dyn / cm, and the refractive index is 1.54;
[0058] S2, add a sodium metasilicate aqueous solution with a concentration of 15wt% to the reactor, add polyvinyl alcohol with a concentration of 1wt%, mix by ultrasonic dispersion, then slowly add 0.1mol / L hydrochloric acid solution, the molar ratio of sodium metasilicate to hydrogen chloride is 1:2, the dropping time is 1h, and ultrasonic dispersion is maintained during the dropping process to form a solution containing crystal nuclei particles with an average particle size of silicon dioxide not exceeding 20nm. Then, an ultrasonic atomization spraying device is used in a vacuum environment to apply the silicon dioxide-containing crystal nucleus solution to the upper surface of the first PVC layer treated in step S1, the ultrasonic operating frequency of the first ultrasonic atomization spraying is 20GHz, and the temperature is 80°C, and then the first microwave vibration heating aqueous solution is performed, the frequency of the first microwave is 2.45GHz, and the temperature is 80°C, so that the product is crystallized and deposited on the surface, evaporated and dried, and a silicon dioxide layer is obtained, and the film thickness is controlled at 135nm by controlling the coating amount;
[0059] S3, the molar ratio of diammine silver hydroxide in the silver ammonia solution to glucose in the glucose solution is 2:1, and 1wt% of polyvinyl alcohol is added, the average particle size of the obtained silver particles does not exceed 20nm, and the silver particles are fed into an ultrasonic atomization spraying device with a metering pump and coated on the upper surface of the silicon dioxide layer, the ultrasonic operating frequency of the second ultrasonic atomization spraying is 20GHz, and the temperature is 80°C, and then a second microwave vibration is performed, the frequency of the second microwave is 2.45GHz, and the temperature is 100°C, so that the product is crystallized and deposited on the upper surface of the silicon dioxide layer, and a silver layer with a thickness of 40nm is obtained by controlling the coating amount, and the metal reflective layer is obtained after evaporation and drying and sintering the nano silver into a film;
[0060] S4, ultrasonic vacuum bonding the second PVC layer to the product obtained in step S3, wherein the temperature of ultrasonic bonding is 90° C. to obtain a film.
[0061] Example 2
[0062] This embodiment provides a method for preparing a film, and the specific steps include:
[0063] The method of Example 1 is the same, except that in step S3, the thickness of the metal reflective layer is 100 nm.
[0064] Example 3
[0065] This embodiment provides a method for preparing a film, and the specific steps include:
[0066] The method of Example 1 is the same, except that in step S3, the thickness of the metal reflective layer is 1000 nm.
[0067] Example 4
[0068] This embodiment provides a method for preparing a film, and the specific steps include:
[0069] The method of Example 1 is the same as that of Example 1, except that "the surface is plasma treated with an ion cleaner, and the dyne value of the surface of the first PVC layer after the treatment is 36 dyn / cm" is changed to "the surface is plasma treated with an ion cleaner, and the dyne value of the surface of the first PVC layer after the treatment is 58 dyn / cm".
[0070] Comparative Example 1
[0071] This comparative example provides a method for preparing a film, and the specific steps include:
[0072] The method of Example 1 is the same, except that in S1, the first PVC layer adopts a flat design and does not need to be embossed, and then the surfaces of the first PVC layer and the second PVC layer are directly cleaned by ultrasound, and then the surfaces are plasma treated by an ion cleaning machine. The dyne value of the surface of the first PVC layer after treatment is 36 dyn / cm, and the refractive index is 1.54, and the dyne value of the surface of the second PVC layer is 36 dyn / cm, and the refractive index is 1.54.
[0073] Comparative Example 2
[0074] This comparative example provides a method for preparing a film, and the specific steps include:
[0075] S1, proceed according to the steps of S1 in Example 1;
[0076] S2, the molar ratio of diammine silver hydroxide in the silver ammonia solution to glucose in the glucose solution is 2:1, and 1wt% of polyvinyl alcohol is added, the average particle size of the obtained silver particles does not exceed 20nm, and the silver particles are fed into an ultrasonic atomization spraying device with a metering pump and coated on the upper surface of the silicon dioxide layer, the ultrasonic working frequency is 20GHz, the temperature is 80°C, and then microwave vibration is performed, the microwave frequency is 2.54GHz, and the temperature is 100°C, so that the product of the silver mirror reaction is crystallized and deposited on the upper surface of the product of step S1, and a silver layer with a thickness of 40nm is obtained by controlling the coating amount, and the nano silver is evaporated and dried and sintered into a film to obtain a metal reflective layer;
[0077] S3, ultrasonic vacuum bonding the second PVC layer to the product obtained in step S2, with the temperature of ultrasonic bonding being 90° C. to obtain a film.
[0078] Comparative Example 3
[0079] This comparative example provides a method for preparing a film, and the specific steps include:
[0080] S1, proceed according to the steps of S1 in Example 1;
[0081] S2, proceed according to the steps of S2 in Example 1;
[0082] S3, ultrasonic vacuum bonding the second PVC layer to the product obtained in step S2, with the temperature of ultrasonic bonding being 90° C. to obtain a film.
[0083] Comparative Example 4
[0084] This comparative example provides a method for preparing a film, and the specific steps include:
[0085] The method of Example 1 is different in that the first PVC layer and the second PVC layer are not subjected to plasma treatment, wherein the dyne value of the surface of the first PVC layer is 32 dyn / cm, and the refractive index is 1.54, and the dyne value of the surface of the second PVC layer is 32 dyn / cm, and the refractive index is 1.54.
[0086] The first PVC layer and the second PVC layer are sprayed unevenly, forming water drops on the surface. The film layer is discontinuous and the film thickness is uneven, making subsequent operations impossible.
[0087] Comparative Example 5
[0088] Comparative Example 5 is an existing film purchased from Guangdong Tianan New Materials Co., Ltd., with a brand name of "0.25mm transparent film", with only one layer and a thickness of 0.25mm.
[0089] Test Case
[0090] (1) The thickness of the base layer was measured using an optical image measuring instrument, and the thickness of each film layer of the functional layer was tested using an Agilent Cary 5000 UV-Vis-NIR spectrophotometer. The specific test results are shown in Table 1.
[0091] Table 1
[0092]
[0093] (2) The transmittance is measured using the WGT-S transmittance meter from Shanghai Shenguang Instruments. The specific light source is iodine tungsten white light. The transmittance formula is: the degree of illumination when the white light is unobstructed is recorded as the transmittance of 100%, and the degree of illumination when the blackboard is blocked for correction is recorded as the transmittance of 0. The transmittance of the test sample is measured and the transmittance is recorded.
[0094] Reflection performance test: TEMP 2000A portable infrared emissivity / reflectivity tester is used to test infrared reflectivity;
[0095] Test of heat insulation effect: In a standard environment, with a temperature of 23°C and a humidity of 50%, a xenon lamp was used to simulate sunlight. The power of the xenon lamp was 1800W. A gray box with an opening of 20×20×20cm was placed 50cm away from the xenon lamp. The prepared film material was laid on the opening. A blackboard of 50×100mm was placed in the middle of the bottom of the box. A temperature sensor was placed on the blackboard. A comparative sample was prepared according to this setting. The light from the xenon lamp was vertically irradiated onto the blackboard through the film sample for 1h, and then the temperature of the blackboard was tested;
[0096] The specific test results are shown in Table 2.
[0097] Table 2
[0098]
[0099] Infrared reflectivity can further prove the thermal insulation performance. The higher the infrared reflectivity, the lower the temperature. It can be seen from the specific data of the embodiment that the film of the present invention is an indivisible whole, and the film prepared by the synergistic effect of each layer can take into account both light transmittance and thermal insulation performance.
[0100] Comparing Example 1 with Comparative Example 1, it can be seen that although Comparative Example 1 still has good light transmittance performance, its heat insulation performance is poor. Specifically, when used as a car film, it will cause the environment inside the car to become stuffy and uncomfortable.
[0101] By comparing Example 1 with Comparative Example 2, it can be seen that although Comparative Example 2 has general heat insulation performance, its light transmittance performance is relatively poor. Specifically, when used as a car film, it will affect the recognition and reaction time of obstacles in front, and there is a great risk.
[0102] Comparing Example 1 with Comparative Example 3, it can be seen that Comparative Example 3 does not have a metal reflective layer. Although the light transmittance can still maintain a certain value, the infrared reflection is very low, the heat cannot be dissipated smoothly, the insulation performance is poor, and it cannot meet the needs.
[0103] Comparison between Example 1 and Comparative Example 4 shows that the dyne value in Comparative Example 4 cannot meet the requirements, the film layer is discontinuous, the film layer thickness is uneven, and subsequent operations cannot be performed.
[0104] Comparison between Example 1 and Comparative Example 5 shows that the film in Comparative Example 5 is an existing film, and both the light transmittance and the heat insulation performance are relatively poor.
[0105] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A film, characterized in that: The film comprises a first thermoplastic base layer, a functional layer, and a second thermoplastic base layer arranged in sequence from bottom to top; in, The first thermoplastic base surface is provided with first grooves and second grooves arranged continuously, a second groove is provided between two adjacent first grooves, the second grooves share a groove edge with the two adjacent first grooves, the spatial shape of the second grooves is the same as the spatial shape of the first grooves, and the groove shapes are inverted with each other, the spatial shape is a triangular pyramid, and the dyne value of the first thermoplastic base surface is 36-58 dyn / cm; The surface of the second thermoplastic base layer is flat, and the dyne value of the surface is 36-58 dyn / cm; The functional layer includes an anti-reflection layer and a metal reflective layer; the metal reflective layer is arranged on the anti-reflection layer; The bottom of the functional layer is in contact with the surface of the first thermoplastic base layer, and the shape of the upper surface of the functional layer is the same as the shape of the surface of the first thermoplastic base layer provided with the first groove and the second groove; The material of the anti-reflection layer includes inorganic oxides and / or inorganic halides.
2. The film according to claim 1, characterized in that: The isosceles triangle on the side of the triangular pyramid is an isosceles right triangle, and the side length of the equilateral triangle on the bottom is 1-5 μm.
3. The film according to claim 1 or 2, characterized in that: The materials of the first thermoplastic base layer and the second thermoplastic base layer are at least one of PVC, PP, PET and PU respectively; and / or, the thickness of the first thermoplastic base layer is 0.1-0.5 mm, and the thickness of the second thermoplastic base layer is 0.05-0.2 mm; and / or, the refractive index of the second thermoplastic base layer is less than or equal to the refractive index of the first thermoplastic base layer; And / or, the thickness of the anti-reflection layer is 120-150 nm; And / or, the material of the metal reflective layer includes at least one of gold, silver and aluminum; And / or, the thickness of the metal reflective layer is 40-1300 nm.
4. The film according to claim 3, characterized in that: The materials of the first thermoplastic base layer and the second thermoplastic base layer are respectively TPU; And / or, the material of the anti-reflection layer includes at least one of silicon dioxide, titanium dioxide, aluminum oxide, and calcium fluoride; And / or, the material of the metal reflective layer is silver; And / or, the thickness of the metal reflective layer is 40-100 nm.
5. A method for preparing the film according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1, preparing a first groove and a second groove arranged continuously on one side surface of a first thermoplastic base layer, and performing plasma treatment, performing plasma treatment on the surface of the second thermoplastic base layer, the dyne value of the surface of the first thermoplastic base layer is 36-58 dyn / cm, and the dyne value of the surface of the second thermoplastic base layer is 36-58 dyn / cm; wherein the second groove shares a notch edge with two adjacent first grooves, the spatial shape of the second groove is the same as the spatial shape of the first groove, and the notch shapes are inverted, and the spatial shape is a triangular pyramid; S2, preparing an anti-reflection layer on the upper surface of the first thermoplastic base layer treated in step S1, and preparing a metal reflective layer on the upper surface of the anti-reflection layer to obtain a functional layer; S3, laminating the second thermoplastic base layer processed in step S1 with the product obtained in step S2 to obtain a laminating film.
6. The preparation method according to claim 5, characterized in that: In S1, the isosceles triangle on the side of the triangular pyramid is an isosceles right triangle, and the side length of the equilateral triangle on the bottom is 1-5 μm.
7. The preparation method according to claim 5, characterized in that: The preparation step of the transmittance-enhancing layer comprises: reacting the raw material components of the transmittance-enhancing layer material in an ultrasonic environment to prepare a crystal nucleus solution with a particle size of less than 20 nm, applying the crystal nucleus solution to one side surface of the treated first thermoplastic layer by first ultrasonic atomization spraying under vacuum, and then performing first microwave irradiation vibration heating to crystallize and deposit the crystal nucleus solution, and obtaining the transmittance-enhancing layer after drying; And / or, the step of preparing the metal reflective layer comprises: applying the nano-metal solution obtained by the silver mirror reaction to the anti-reflection layer by a second ultrasonic atomization spraying under vacuum, and then performing a second microwave irradiation vibration heating to make the nano-metal solution crystallize and deposit on the surface of the anti-reflection layer, drying and performing a second microwave irradiation, and sintering the product after the crystallization deposition to obtain a metal film layer; And / or, in step S3, the specific step of laminating includes: laminating multiple groups of double-wheel laminating film layers by ultrasonic method under vacuum to obtain laminating films.
8. The preparation method according to claim 7, characterized in that: The frequency of the first microwave is 2-3 GHz, and the temperature is 50-150° C.; And / or, the frequency of the second microwave is 2-3 GHz, and the temperature is 100-150°C.
9. The preparation method according to claim 7, characterized in that: The temperature of the ultrasonic bonding is 50-160°C.
10. Use of the film described in any one of claims 1 to 4 or the film prepared by the preparation method described in any one of claims 5 to 9 in sun-proof and heat-insulating films.
Citation Information
Patent Citations
Method and system for packaging OLED through coating roasting lamination die casting
CN113611813A
Thermal control ETFE film and preparation method and application thereof
CN118952804A
Thermal -insulated auto film
CN207808678U
High-reliability temperature-resistant aluminized base material film
CN213167175U
Heat-insulating PE (polyethylene) film
CN216466581U